ปัญหากฎหมายเกี่ยวกับเลขานุการบริษัทตามกฎหมายว่าด้วยหลักทรัพย์และตลาดหลักทรัพย์ - บ่มไล่ อรุณชัย; รื่นเริง พิมพ์ใจ; เซอร์ซันซี สมจิตต์ (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: To study the securities and exchange laws, analyse the legal problems on securities and exchange related to the company secretary, and to recommend solutions to legal problems on securities and exchange related to the company secretary. METHODS: Documentary research by conducting research on legal provisions for company secretary in Thailand and other countries from various documents, academic texts, articles, thesis, as well as electronic information on various websites related to the company secretary for an analysis to obtain conclusions and recommendations that w0uld be able to amend the legal criteria to be systematically consistent and appropriate. RESULTS: The Act on Securities and Exchange did not outline features and prohibited characteristics of the company secretary and the provisions on the role of the company secretary were insufficient and inconsistent with the current situation. CONCLUSIONS: Securities and Exchange Act would better outline specifically and sufficiently roles and functions of company secretaries to be consistent with current situations.